POLITICAL CONFLICTS: ANALYSIS OF GENERAL PRINCIPLES OF SETTLEMENT FROM THE PERSPECTIVE OF NATIONAL AND INTERNATIONAL SECURITY - V. N. Panin; A. S. Konstantinova (Современная наука и инновации)
The article analyzes the possible ways of resolving political conflicts, which are a kind of relations in the field of politics and in essence Express a competitive claim of two or more subjects, challenging each other's distribution ofpower or resources. Different socio-political forces in their desire to acquire power, redistribute it or at least influence it, resort to confrontation: open or veiled clash. Victory in a political conflict promises, at least, a change in the political status, possible political prospects for the development of society. A number of principles of political conflict settlement, both domestic and international, are revealed. It is proved that the principle of gradualness is important in the settlement of a political conflict, which involves the gradual preparation of the parties to the beginning of a direct settlement.